2006
DOI: 10.1177/1368430206062074
|View full text |Cite
|
Sign up to set email alerts
|

Attributions to Discrimination and Self-Esteem: The Role of Group Identification and Appraisals

Abstract: This study tested the hypothesis that appraisals of discrimination (i.e. its perceived severity, global aspects, stability, and uncontrollability) mediate the relationship between attributions to discrimination and personal self-esteem. It also tested three models of how ethnic group identification is related to discrimination attributions, discrimination appraisals, and personal self-esteem. In a cross-sectional study of 160 Latino-American students, group identification was positively related to attributing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
130
0
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(153 citation statements)
references
References 43 publications
14
130
0
9
Order By: Relevance
“…To our knowledge, all other previous research on the role of centrality in psychological distress has focused on visible identities (primarily race). In both cross-sectional and longitudinal studies, greater centrality of ethnic identity has been related to lower levels of psychological distress among African Americans (e.g., Sellers, Caldwell, Schmeelk-Cone, & Zimmerman, 2003;Sellers, Smith, Shelton, Rowley, & Chavous, 1998;Yip, Seaton, & Sellers, 2006 Eccleston & Major, 2006;Major, Quinton, & Schmader, 2003;McCoy & Major, 2003).In the current research we predicted that greater centrality of the identity would be related to increased psychological distress. While previous research has suggested that identities that are more central to the self may have benefits for psychological well-being because they offer people a source of social support and can provide external attributions for negative events (e.g., Bourguignon, Seron, Yzerbyt, & Herman, 2006;Crocker & Major, 1989;Cross, 1991), we predicted that this is not the case for those whose identity is concealable.…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…To our knowledge, all other previous research on the role of centrality in psychological distress has focused on visible identities (primarily race). In both cross-sectional and longitudinal studies, greater centrality of ethnic identity has been related to lower levels of psychological distress among African Americans (e.g., Sellers, Caldwell, Schmeelk-Cone, & Zimmerman, 2003;Sellers, Smith, Shelton, Rowley, & Chavous, 1998;Yip, Seaton, & Sellers, 2006 Eccleston & Major, 2006;Major, Quinton, & Schmader, 2003;McCoy & Major, 2003).In the current research we predicted that greater centrality of the identity would be related to increased psychological distress. While previous research has suggested that identities that are more central to the self may have benefits for psychological well-being because they offer people a source of social support and can provide external attributions for negative events (e.g., Bourguignon, Seron, Yzerbyt, & Herman, 2006;Crocker & Major, 1989;Cross, 1991), we predicted that this is not the case for those whose identity is concealable.…”
mentioning
confidence: 61%
“…In both cross-sectional and longitudinal studies, greater centrality of ethnic identity has been related to lower levels of psychological distress among African Americans (e.g., Sellers, Caldwell, Schmeelk-Cone, & Zimmerman, 2003;Sellers, Smith, Shelton, Rowley, & Chavous, 1998;Yip, Seaton, & Sellers, 2006). On the contrary, work examining other stigmatized identities, including women and Latinos, as well as some additional work done with African Americans, has shown either a negative or null relationship between centrality-also called identity importance or group identification -and psychological well-being (e.g., Eccleston & Major, 2006;Major, Quinton, & Schmader, 2003;McCoy & Major, 2003).…”
Section: Direct Effects Of Stigma-related Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies should further investigate the contradictory effects of these attributions on self-esteem in "real life" by examining the different pathways underlying them (cf. Eccleston & Major, 2006). These studies could also look at the social costs of making attributions to discrimination (Kaiser & Miller, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the experiences and effects of discrimination are most often examined in experimental paradigms, whereby a lab simulation of discrimination is portrayed to participants (Foster, 2001;Foster & Tsarfati, 2005;Kaiser, Major & McCoy, 2004;Mallet & Swim, 2005;Schmitt, Branscombe & Postmes, 2003) or it is examined at one point in time with questionnaires (e.g., Branscombe et al, 1999;Clark, 2006;Eccleston & Major, 2006;Foster, 2000;Lightsey & Barnes, 2007;Kaiser & Miller, 2004;Peters, 2006;Schmitt, Branscombe, Kobrynowicz & Owen, 2002;Scott & House, 2005). Indeed, such methodologies are important for clarifying causation and how the recall of past events can currently affect us.…”
Section: Introductionmentioning
confidence: 99%